Polymorphism of Microsatellite markers and ‎Their Association with Egg Production Traits in ‎Iraqi Chickens (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The present study was conducted on local Iraqi chickens and two strains of commercial laying hens (ISA Brawn and Ross Hen) as control. To estimate genetic Diversity using microsatellites and their association with egg production traits, three microsatellites markers, located on 1, 5 and E5C10 chromosomes were used in pesent study. A total of 100 varieties of three chicken populations were genotyped for three microsatellite markers by polymerase chain reaction (PCR) to evaluate the genetic Diversity (GD) among populations using Nei Index similarity mean. The present study show that local chicken populations were more diverse than control populations. Genetic Diversity among populations was obtained using Nei Index similarity mean. The present results indicate that the Highest GD among local chickens (0.82) and the lowest GD (0.4) and when comper local chickens with control strains found that the highest GD was (0.76) when comper with ISA Brawn, and (0.702) when comper the study population with Ross Hen strain and the lowest GD was (0.673) when comper with ISA Brawn strain, (0.661) when comper the study population with Ross Hen  strain, that’s mean the Three microsatellite genetic markers applied in the present study success to reveal high degree of similarity among the three population used here. The genetic distance revealed that local chickens are mostly related to ISA Brawn strain more than Ross Hen strain